Retreatment with Ozurdex for Macular Edema Secondary to Retinal Vein Occlusion. Issue 1 (January 2014) - Coscas, Gabriel; Augustin, Albert; Bandello, Francesco; de Smet, Marc D.; Lanzetta, Paolo; Staurenghi, Giovanni; Parravano, Maria Cristina; Udaondo, Patricia; Moisseiev, Elad; Soubrane, Gisele; Yatziv, Yossi; Loewenstein, Anat
Purpose: To review the current practice of retreatment with Ozurdex injections in patients with macular edema (ME) secondary to retinal vein occlusion (RVO), and to recommend simple guidelines for Ozurdex reinjection in management of RVO. Methods: This was a multicenter retrospective study of patients who received more than 2 Ozurdex injections for the treatment of ME in RVO. Recorded parameters included percent of patients with a 15-letter gain, visual acuity (VA) improvement from baseline, change in central macular thickness (CMT), time to reinjection, and occurrence of any complications. Results: A total of 128 patients were included, 58 (45.3%) with central RVO (CRVO) and 70 (54.7%) with branch RVO (BRVO). Mean interval for Ozurdex reinjection was 5.9 months following the first injection and 8.7 months following the second. A >15-letter gain in VA was observed in 34 (48.8%) patients with CRVO and 16 (28%) patients with BRVO. Mean overall VA improvement at month 6 did not show significance (p>0.05); however, a significantly better mean VA improvement was seen in treatment-naïve eyes (p<0.03). The CMT was significantly reduced compared to baseline. The mean CMT decreased by 214.6 μm in eyes with BRVO (n = 53) and by 355.1 μm in eyes with CRVO (n = 63) (p = 0.002). Complication rates were very low. Conclusions: Repeated injections of Ozurdex are effective and have a favorable safety profile. In current practice, the retreatment interval with Ozurdex injections might be too long, precluding the full therapeutic potential of this treatment modality. A strategy for managing RVO patients treated with Ozurdex on an as-needed basis is provided.